KARAKTERISTIK KOMITE AUDIT DAN RISIKO PENGAMBILAN KEPUTUSAN PADA BANK SYARIAH PERIODE 2013-2020 - Fetri Wahyu Handayani; Adhelia Desi Prawestri (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
The purpose of this study was to analyze how the influence of audit committee characteristics, namely audit committee size, audit committee independence, audit committee meetings, audit committee educational background, audit committee age, and audit committee gender at decision-making risk proxied by NPF in Islamic Banks in the 2013 period -2020. This study used a purposive sampling technique with 11 samples of Islamic banks. The results showed that audit committee size had a positive effect on decision-making risk, audit committee independence damaged decision-making risk, audit committee meetings damaged decision-making risk, the educational background damaged decision-making risk, the age of the audit committee had a positive effect on decision-making risk, and the gender of the audit committee damaged decision-making risk.